Respostas

2014-01-29T18:18:48-02:00
Δ = b² -4ac
Δ = 6² -4 *1 * 9
Δ = 36 -36
Δ = 0
x' = (-b + √∆)/ 2a
(-6 + 0)/2 * 1
(-6 + 0)/2
-6/2
-3
x'' = (-b - √∆)/ 2a
(-6 - 0)/2 * 1
(-6 - 0)/2
-6/2
-3

\[\boxed{S=-3,-3}\]

2014-01-29T18:21:04-02:00
É só utilizar a fórmula bhaskara

x²+6x+9=0 ~> a = 1 , b = 6 , c = 9

Δ = b² - 4ac
Δ = 6² - 4.1.9
Δ = 36 - 36
Δ = 0    ~> as raízes serão iguais

x = -b ± √Δ
         2a

x = -6 ±0
         2.1

x = -6 
± 0
         2

x' = -6 + 0 = -6  = -3           x" = -6 - 0 = -6 = -3
          2        2                             2       2

S =  {-3;-3}
1 5 1